A germanium nanoparticles/molybdenum disulphide (MoS2) nanocomposite as a high-capacity, high-rate anode material for lithium-ion batteries. Issue 8 (2nd February 2017) - Hsieh, Meng-Hsun; Li, Guo-An; Chang, Wei-Chung; Tuan, Hsing-Yu
Abstract : A facile synthesis of Ge/MoS2 nanocomposites is developed by blending Ge nanoparticles into MoS2 nanosheets in solution at room temperature followed by annealing at 350 °C. Abstract : A facile synthesis of Ge/MoS2 nanocomposites is developed by blending Ge nanoparticles into MoS2 nanosheets in solution at room temperature followed by annealing at 350 °C. The decoration with Ge nanoparticles in this compound can synergistically improve the electrochemical performance of LIBs because of increased conductivity and structure stability. Ge/MoS2 nanocomposites exhibit a high reversible capacity of 1362 mA h g −1 cycled at 0.2 A g −1 after 50 cycles. Even at high rate capability (>1 A g −1 ), the battery performance of Ge/MoS2 from 0.2 A g −1 to 15 A g −1 is superior to the performances of the reported graphene-based and other nanoparticle-decorated MoS2 anodes. Finally, a coin-type full-cell with a high areal capacity (∼3 mA h cm −2 ) and a high volumetric capacity (∼1700 mA h cm −3 ) was also achieved with a Ge/MoS2 anode and a Li(MnCoNi)O2 cathode.